The fault in our stars - Green, John, 1977- (New York, N.Y. : Penguin Books, an imprint of Penguin Group (USA) LLC, 2014)
Sixteen-year-old Hazel, a stage IV thyroid cancer patient, has accepted her terminal diagnosis until a chance meeting with a boy at cancer support group forces her to reexamine her perspective on love, loss, and life.
Wilson's Senior High School, November 2012
School Library Journal starred, February 2012
Booklist starred, January 2012
Horn Book Starred, March 2012
Library Media Connection starred, August 2012
Bulletin of the Center for Children's Books starre, May 2012
Keywords: Cancer -- Patients -- Juvenile fiction; Terminally ill -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Cancer -- Patients -- Fiction; Terminally ill -- Fiction; Interpersonal relations -- Fiction; Love -- Fiction; Cancer -- Patients -- Fiction; Terminally ill -- Fiction; Interpersonal relations -- Fiction; Love stories; Love stories